Leukotrienes B4, C4, D4 and E4 in the exhaled breath condensate (EBC), blood and urine in patients with pneumoconiosis - Pelclová, Daniela; Fenclová, Zdenka; Vlcková, Stepánka; Lebedová, Jindriška; Syslová, Kamila; Pecha, Ondrej; Belácek, Jaromír; Navrátil, Tomáš; Kuzma, Marek; Kacer, Petr (Industrial health, 2012)
Leukotrienes (LTs) are involved in the pathogenesis of lung fibrosis and were increased in exhaled breath condensate (EBC) of the patients with pneumoconiosis. However the possible influence of extra-pulmonary disorders on the EBC markers is not known. Therefore in parallel with EBC, LTs' levels in the plasma and urine were measured in patients with pneumoconiosis (45 × asbestos exposure, 37 × silica exposure) and in 27 controls. Individual LTs B4, C4, D4 and E4 were measured by liquid chromatography - electrospray ionization - tandem mass spectrometry (LC-ESI-MS/MS). In EBC, LT D4 and LT E4 were increased in both groups of patients (p<0.001 and p<0.05), comparing with the controls. Both LT B4 and cysteinyl LTs were elevated in asbestos-exposed subjects (p<0.05). Asbestosis with more severe radiological signs (s1/s2-t3/u2) and lung functions impairment has shown higher cysteinyl LTs and LT C4 in the EBC (p<0.05) than mild asbestosis (s1/s0-s1/s1). In addition, in the subjects with asbestosis, cysteinyl LTs in EBC correlated with TLC (-0.313, p<0.05) and TLCO/Hb (-0.307, p<0.05), and LT C4 with TLC (-0.358, p<0.05). In pneumoconioses, EBC appears the most useful from the 3 fluids studied.
Keywords: lidé středního věku; leukotrien E4; leukotrieny; silikóza; stupeň závažnosti nemoci; Male; Asbestosis; Leukotriene B4; Radiography; radiografie; lidé; Respiratory Function Tests; senioři; leukotrien D4; Severity of Illness Index; Aged; leukotrien B4; dechové testy; Silicosis; ženské pohlaví; Leukotriene D4; respirační funkční testy; leukotrien C4; Leukotriene C4; azbestóza; Leukotriene E4; Breath Tests; Leukotrienes; mužské pohlaví; Middle Aged; Humans; Female